500 Cases of High-intensity Focused Ultrasound (HIFU) Ablated Uterine Fibroids and Adenomyosis - Cherng-Jye Jeng; Kae-Ying Ou; Cheng-Yu Long; Linus Chuang; Chin-Ru Ker (Elsevier, 2020)
Objective: Clinical outcomes of 500 high-intensity focused ultrasound (HIFU)-treated uterine fibroids and adenomyosis are analyzed and presented. Materials and methods: This is a retrospective cross-sectional analysis from a single tertiary medical center. From April 2015 to October 2018, 546 cases were enrolled for the study. After excluding 46 patients with less than 3 months of follow-up period, there were 404 fibroids, 149 adenomyosis and 53 mixed conditions entered for analysis. The patients' uterine fibroids and adenomyosis were treated by HIFU according to Chongqing Haifu protocol, with 12 cm diameter transducer of focal length 10-16  cm at 0.8 or 1.6 MHz T2-weight MRI imaging was rendered prior to and 3 month post treatment to assess lesion volume change using non-perfusion volume, which was the primary outcome. Secondary outcomes including quality of life, subjective satisfaction, adverse events and pregnancy rate were determined using self-reported questionnaires. The mean follow up period ranged from 3 to 38 months with an average of 21 months. Results: Three months after HIFU-treated uterine fibroids and adenomyosis, the lesion size reduced 40.2% and 46.3%, respectively. Symptoms all improved with better quality of life for the fibroid group, while those with adenomyosis or combined diseases benefit the most from pain control. Serum CA125 decreased significantly for all studied groups, and LDH only showed improvement for fibroids group. Number of adverse events is comparable to Chongqing data (approximately 10.2%), with mostly mild and self-resolving conditions. No permanent sequelae or death was documented. Twelve pregnancies are reported in this cohort. Conclusion: HIFU is safe and effective in treating uterine fibroids and adenomyosis. The results are reproducible if standardized treatment schedules are followed. It is a promising treatment alternative with the advantages of precision, non-invasiveness, rapid recovery and readiness for pregnancy.